The Worlds of Alfonso the Learned and James the Conqueror : Intellect and Force in the Middle Ages - Burns, Robert I., 1921-2008 (Book collections on Project MUSE., 1985)
The thirteenth-century monarch Alfonso the Learned of Castile and his contemporary rival James the Conqueror, of Aragon-Catalonia, are key figures who made enduring contributions to Western civilization--although neither is well known to American students. This book explores the contrasts and convergences not only of the kings but of the scholarly-cultural with the military-commercial society.Originally published in 1985.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.